Risk Factors for Preoperative and Postoperative Hearing Loss in Children Undergoing Pressure Equalization Tube Placement. (4th April 2014) - Sidell, Douglas; Hunter, Lisa L.; Lin, Li; Arjmand, Ellis
Abstract : Objective: Pressure equalization tube (PET) placement is the most common surgical procedure performed during childhood. Current guidelines recommend more prompt management of children with otitis media with effusion who are at greater risk for speech‐language and developmental problems. This study was designed to examine risk factors for continued post‐PET hearing loss in a large pediatric clinical sample. Study Design: Retrospective analysis using the electronic medical record. Setting: Tertiary care children's hospital. Subjects: Pediatric patients undergoing PET placement between January 2009 and October 2012 who had audiometric tests. Methods: Demographics, patient diagnoses, and hearing loss information were extracted. Multivariate binary logistic regression models were used to identify associations between patient‐specific characteristics and the presence of hearing loss. Results: In total, 3949 children with 4598 audiology visits were included (2357 males and 1592 females; mean age, 3.3 years), and 1272 preoperative and 3329 postoperative audiograms were performed. Using multivariate modeling, the only variable significantly associated with preoperative hearing loss was low tympanometric static acoustic admittance. Postoperative hearing loss was positively associated with patient age, preoperative hearing loss, lower tympanometric equivalent canal volumes, and Down syndrome. Other factors, including cranial/facial anomalies, low birth weight or prematurity, allergies, and asthma, were not determined to be risk factors for hearing loss. Conclusion: Our results support hearing testing to identify candidates for PET surgery and to determine treatment effectiveness after surgery, since hearing loss cannot be predicted on the basis of risk or demographic factors. These data have important preoperative counseling and postoperative management implications.